The Role of Promotions on Food Delivery Service Platforms in Shaping Generation Z’s Sustainable Behavior in Managing Food Waste - Gede Reiki Nobel Wedatama Mahardika; Ida Bagus Raka Suardana (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
The rapid development of digital technology has transformed marketing practices, particularly in competitive sectors such as the food industry. However, prior studies report inconsistent findings regarding the influence of digital marketing and brand awareness on purchase decisions, highlighting the need for evidence in specific local contexts. This study examines the effects of digital marketing and brand awareness on consumer purchase decisions at PT Bali Food Industry, a frozen fruit producer in Bali. A quantitative approach was employed using purposive sampling, resulting in 176 valid respondents who had seen the company’s advertisements and purchased its products. Data were collected through an online questionnaire using a five-point Likert scale and analyzed using multiple linear regression with SPSS, following reliability and classical assumption tests. The results indicate that digital marketing positively and significantly affects purchase decisions (B = 0.239; β = 0.382; t = 6.064; p < 0.001) and that brand awareness also has a positive and significant effect (B = 0.387; β = 0.426; t = 6.763; p < 0.001). Simultaneously, both variables significantly influence purchase decisions (F = 85.418; p < 0.001), explaining 49.5% of the variance (R² = 0.495). These findings suggest that optimizing digital marketing and strengthening brand awareness can meaningfully enhance consumer purchase decisions.